Feasibility Study of Chatime Franchise Business - Dini Vientiany; Annisa Riani Simbolon; Nur Afiqah Nabila; Hasbi Rizky Rawy (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The development of the contemporary beverage industry in Indonesia shows rapid growth, especially in pearl milk tea-based products. One brand that has been able to maintain its existence is Chatime, a Taiwanese tea beverage chain that has more than 2,300 outlets in 38 countries, including around 460 outlets in Indonesia by 2025. This study aims to analyze the feasibility of the Chatime franchise business by reviewing various aspects, including market and marketing aspects, legal aspects, technical and operational aspects, management aspects, financial aspects, sharia and halal aspects, as well as economic, social, and environmental aspects. The method used is a qualitative descriptive approach using secondary data obtained from scientific literature, media reports, and official company documents. The results of the analysis show that Chatime has a clear target market, a standardized operational system, and promising financial prospects, even though it requires a relatively large initial investment of around IDR 1.4 billion. Overall, the Chatime franchise business is considered feasible to run and has the potential for sustainability in Indonesia.